Fractionation of Dioscorea bulbifera bulbil protein, its antioxidative potential and inhibitory effects on Carbohydrate-hydrolyzing enzymes - Oludele ODEKANYIN; Eniola BADMUS; Deborah Akinyemi (Trends in Pharmaceutical Sciences, 2024)
The study fractionated Dioscorea bulbifera bulbil proteins, determined the fractions inhibitory potential against α-amylase and α-glucosidase activity, and evaluated their antioxidative activity in-vitro. Dioscorea bulbifera bulbil flesh was homogenized in Phosphate Buffer Saline (pH7.2), centrifuged at 10,000 xg for 30 min and supernatant was subjected to ammonium sulphate fractionation. Three fractions (25%, 60% and 90%) were produced and their hemagglutinating activity, blood group and sugar specificity were determined. Ability of the fractions to inhibit α-amylase and α-glucosidase activity was investigated. Antioxidative properties were evaluated using DPPH, Nitric oxide and hydroxyl radicals scavenging assay. Their reducing power, total antioxidant capacity and ferrous chelating activity were also evaluated. Data obtained revealed the presence of lectin in the crude protein extract, 25% and 60% protein fractions. The lectin agglutinated rabbit blood erythrocyte better than human blood groups erythrocyte. Protein fraction (60%) has no hemagglutinating activity towards human blood erythrocyte. Mannose completely inhibited the hemagglutinating activity.  Alpha-amylase and α-glucosidase activities were inhibited by 25% and 60% protein fractions with no significant difference. But their inhibitory action was better than that of acarbose. All the free radicals tested were scavenged by the fractions to various degrees. Sixty percent protein fraction could not scavenge nitric oxide but it was a better scavenger of hydroxyl radical. No activity was recorded for 90% protein fraction. The results showed the anti-diabetic potential of the protein fractions and can be harnessed for possible development of therapeutics agents for the treatment of diabetes and oxidative stress associated ailments.